KONSEP PENDIDIKAN AL-GAZALI DAN AL-ZARNUJI - Wahyuddin, Wahyuddin (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2018)
The concept of education according to Imam al-Ghazali and al-Zarnuji is a process of the soul to understand the meaning of something as an effort to form akhlakul karimah to bring closer (taqarrub) to God in order to achieve salvation in the world and in the hereafter. Both concepts emphasize the moral requirements as the main base, but al-Gazali is more likely on the teacher (al-Mu'allim). While al-Zarnuji stressed the moral requirements, both on teachers and students. That is, the interaction of teachers and students in the learning process must uphold ethics without having to turn off the creativity and dynamics of learning. Thus, it is clear that the two characters make morality as a basis for their thinking in conducting educational thinking. The thought of Islamic education based on morals is relevant to life in the modern era, considering the Islamic society is facing increasingly complex problems. Education based on morals is expected to be a solution for both teachers and learners.